Human pannexin mutations and their implications in erosive osteoarthritis - Justin Tang; Jason Lu; Danielle Johnston; Kazuyuki Hoshijima; Brent Wakefield; Donglin Bai; Peter B. Stathopulos; Roger J. Thompson; Alexander W. Lohman; Michael J. Jurynec; Frank Beier; Silvia Penuela (Proceedings of the National Academy of Sciences, 2026)
Erosive hand osteoarthritis (EHOA) is a chronic joint disease characterized by severe inflammation and degeneration of cartilage and bone tissue. As this disease is multifactorial in nature, the molecular mechanisms that influence its pathogenesis are unclear, leading to a lack of disease-modifying therapies. However, by screening 40 families with a dominant inheritance pattern for EHOA, we identified two independent germline heterozygous mutations that associated with EHOA onset: PANX1 [c.G455A:p.R152H] and PANX3 [c.G71A:p.R24H]. Pannexin 1 (PANX1) and Pannexin 3 (PANX3) are mechanosensitive channel-forming glycoproteins that pass various metabolites and ions such as adenosine triphosphate (ATP) and calcium to regulate numerous physiological and cellular processes including tissue development, cell differentiation, and homeostasis. In this study, we report that electrophysiological recordings, ATP release, and basal dye uptake assays revealed increased channel activity of the PANX1 R152H variant, which led to increased cytotoxicity following long-term expression. In contrast, R24H mutant PANX3 channels exhibited a loss-of-function in mechanically stimulated dye uptake assays. Under stable, moderate expression conditions, this reduction in channel activity was associated with decreased cell growth, whereas overexpression led to increased cell death. In vivo, R24H expression in zebrafish embryos increased apoptosis and upregulation of p21 and osteogenic genes. Together these findings demonstrate that two mutations with opposing alterations in PANX channel activity, hyperactivity in R152H PANX1 and loss-of-function in R24H PANX3, can converge on degenerative cellular outcomes. Collectively, we report the first germline PANX3 mutation associated with disease and provide the first evidence linking PANX1 and PANX3 mutations to human erosive osteoarthritis.